Analisis Pelaksanaan Kebijakan Pemerintah Daerah dan Faktor Penghambat dalam Upaya Penanggulangan Stunting di Indonesia - Anggraeni, Nuri; Astuti, Widya (IPTEKIN Jurnal Kebijakan Pembangunan dan Inovasi, 2023)
Based on WHO classification, the prevalence of stunting in Indonesia is still high, at 21.6%. Stunting is a severe nutritional problem, it can cause impaired brain development so that their intelligence and cognitive function will decrease. In the long term, stunting can cause a decline in the quality of human resources in Indonesia. Therefore, the government and society must work together to overcome this problem. The purpose of this article is to find out and analyze the implementation of local government policies and inhibiting factors in efforts to prevent and overcome stunting issues in Indonesia. The method used in this article is a literature review of articles published with sources from Google Scholar, PubMed, and Elsevier. The results of the review show that government programs for overcoming stunting can be grouped into three, there is counseling, providing additional food, and providing health facilities. Detention that can hinder consist of a lack of human resources, facilities, and funding sources, and low participation of knowledge and awareness from the community.